Organic management of tuberous intercrops for resilience, higher yield and profit from coconut plantations: Insights from validation experiments in Kerala, India - Suja, G.; Jaganathan, D.; Byju, G. (Journal of Plantation Crops, 2023)
Fifteen on-farm experiments were conducted in tropical tuber crops intercropped in coconut gardens in Thiruvananthapuram, Kollam and Pathanamthitta districts, Kerala, during 2018-2021 for validation of organic production technologies. The validation experiments were performed under the aegis of the ICAR-Central Tuber Crops Research Institute, Thiruvananthapuram, in a project funded by the Coconut Development Board, Kochi, Kerala. Three treatments viz., T1: organic farming technology (OF), T2: POP recommendation (POP) and T3: farmer’s practice (FP) were evaluated in cassava, elephant foot yam and greater yam intercropped with coconut. System productivity and profitability were worked out for the diﬀerent treatments based on yield and income from coconut and tuber crops in the respective treatments. Pooled analysis indicated that the coconut yield under intercropping with tuber crops in organic mode was high by 7-13% in comparison to monocrop of coconut maintained by the farmers. Tuber yield under organic management was superior over POP by 14% and FP by 27%. On an average, the net income from coconut-tuber crop intercropping system under organic management was ₹ 2,36,133 ha-1, whereas it was ₹ 1,56,904 ha-1 in POP and ₹ 1,32,706 ha-1 in FP and significantly outperformed sole coconut (₹ 7,764 ha-1). Thus, the results indicated that organic management of coconut-tuber crop system oﬀered resilience with higher system productivity and profitability.